On writing about illness in Kuwait. A discussion with Shahd Al Shammari - Marion Breteau (L’Année du Maghreb)
On the occasion of the release of Shahd Al Shammari’s latest book, Head Above Water: Reflections on Illness (2022) in Kuwait, Marion Breteau went to meet the author to interview her about the experience of writing intimacy. Shahd Al Shammari, who is a professor of English literature at the Gulf University for Science and Technology of Kuwait, has already published several works of fiction and academic works in the field of disability studies and gender studies. In this interview, she discusses her latest book and the experience of autoethnographic writing from a feminist perspective. Intimacy, in Head Above Water, is thus her own: by tracing the evolution of multiple sclerosis she suffers from since the age of 18, the narrative has as its centrality the problematic of the sick body. In the hands of doctors, through medical discourses, between the four walls of hospitals, Shahd Al Shammari explores the transformations of her adolescent body, she experiences her first love stories, while taking her first steps into the academic world. The intimate, through the body, becomes the vehicle of her personal construction and her gender identity. With this book, she highlights the tension between intimacy and publicity through the act of writing. This tension is all the more acute because, in Kuwait, the act of writing can undermine local authors who, like her, write in English, a linguistic choice often perceived as a threat to the country’s cultural and linguistic identity. From then on, writing the intimate becomes a political act. It can also become a “politics of love” when expressing pain and anger is less important than raising awareness and inviting to solidarity through writing and teaching. The interview first looks at the context of the Covid-19 pandemic and how it has led to a rethinking of teaching and research: stripped of their research resources and classrooms, many academics have indeed had to reinvent themselves. This is the case for S. Al Shammari who took this opportunity to look at the Head Above Water project. The interview goes on to discuss the stages of the book’s narrative construction, and then its reception by the Kuwaiti public. The author discusses her choice to write in English as well as her theoretical positions, which are strongly rooted in a literary feminist perspective. Given the advocacy nature of the autoethnographic approach, it made sense for her to adopt this methodology. The interview also discusses the reception of the book in the research community. S. Al Shammari points to the scarcity of disability studies, which, as she explains, reflects a form of patriarchal academic ableism. Finally, this critique serves to highlight the role of teaching in her academic career. It is through classroom exchanges, and the practice of transmission, that what could be rage is transformed into a tool for cohesion and enlightenment, in a context where equal opportunity is impacted by gender roles and where "non-visible" disability is underestimated. Eventually, the editorial and academic fields become the receptacles of intimacy building through the very experience of putting it into words. Although the book is the restitution of a story that takes place mostly in Kuwait, it is nonetheless a shared testimony, a point of honor on which the author insists, aware of the orientalist gaze to which her work is subjected.